Embryonic infection with the endogenous avian leukosis virus Rous-associated virus-0 alters responses to exogenous avian leukosis virus infection. - Crittenden, L B (1987)
We inoculated susceptible chicken embryos with the endogenous avian leukosis virus Rous-associated virus-0 (RAV-0) on day 6 of incubation. At 1 week after hatching, RAV-0-infected and control chickens were inoculated with either RAV-1 or RAV-2, exogenous viruses belonging to subgroups A and B, respectively. The chickens injected with RAV-0 as embryos remained viremic with exogenous virus longer and either failed to develop type-specific humoral immunity to exogenous virus or developed it later than the control chickens not inoculated with RAV-0. The RAV-0-injected chickens also developed neoplasms at a much higher frequency than did the control chickens. We suggest that the lower immune responses of the RAV-0-injected chickens were due to an immunological tolerance to envelope group-specific glycoproteins shared among endogenous and exogenous viruses.